Monomeric structure characterization of different sources biomass lignin - Halim, N. A. A. (Trans Tech Publications Ltd., 2016)
Utilization of lignocellulosic biomass as the source for lignin could possibly gain an interest and future demands due to its potential to be converted into high value added compound based on their structural characteristics. Three types of biomass lignin originated from oil palm empty fruit bunch fiber (OPEFB), coconut husk and kenaf fibers are subjected to an alkaline hydrolyzation in steam autoclave and precipitation by phosphoric acid. The structural characterization of all three lignin samples performed by FTIR spectroscopy and HNMR analysis suggests that OPEFB is primarily consist of syringyl (S) units while coconut husk and kenaf fiber were consisted of guaiacyl (G) units. However, all three samples exhibit small portion of phydroxyphenyl propane (H) units.